Titanium(IV) Inclusion as a Versatile Route to Photoactivity in Metal–Organic Frameworks. Issue 11 (26th August 2019) - Mancuso, Jenna L.; Hendon, Christopher H.
Abstract: Titanium‐containing metal–organic frameworks (MOFs) are known to perform light‐promoted chemical transformations. Formation of these frameworks, accessed either natively or via transmetallation, can instill beneficial photocatalytic properties in previously photo‐inert scaffolds. Band edge diagrams coupled with their density of states illustrate the persistent nature of the accessible titanium d‐states at the conduction band edge, independent of linker identity. In essentially all of these Ti‐containing frameworks, the valence band edge localizes on the organic component, permitting facile modulation of the band gap. In sum, the spatial separation of photogenerated excitons will be observed in both the native and titanium(IV)‐substituted MOFs, and this exciton pair is useful in photocatalysis. Abstract : Light metals make light work . Electronic properties of titanium(IV)‐containing metal–organic frameworks generated through direct synthetic methods or metal substitution are evaluated with density functional theory. Band edge engineering discussed through the density of states suggests that incorporation of titanium(IV) is a general strategy yielding exciton separation in metal–organic frameworks, complemented by an adjustable band gap.